Identification of Hydrothermal Aquifer Zone using Geo-Electrical Method in Kaloling Sinjai District - Lantu L; D. A. Suriamihardja; Tri Harianto; A. M. Imran (INDONESIAN JOURNAL OF APPLIED PHYSICS, 2015)
Geothermal energy is one of the natural resources which  emerged on the subsurface ofthe earth can be in a gaseous form (the vapor heat) or in the form of hydrothermal. The geothermal Panggo that located at watersheds of Kalamisu river, was one of the three sources of hydrothermal system  existing in district Sinjai East. The existence of the geothermal system in this area will much give many advantagest if managed optimally. This research aims to map the spread of the hydrothermal aquifer zone at the subsurface and it potentials in Panggo village base on electrical properties. Methods used in this research were geo-electrical using Wenner and Schlumberger configurations.At all these research area, it is found the presence of zones which has low resistivity (< 20 Ωm), and it is interpreted as the spread of hydrothermal zones. The hydrothermal system appears at subsurface allegedly caused by the geological fault of Kalamisu across this region.